Implementation of the REHAB Program (Gradual Payment Plan) in Reducing JKN Contribution Arrears at Solok City BPJS Health: Implementasi Program REHAB (Rencana Pembayaran Bertahap) dalam Meringankan Tunggakan Iuran JKN pada BPJS Kesehatan Kota Solok - Rona Jauza; Rahmadani Yusran (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2024)
This research aims to analyze the implementation of the REHAB (Gradual Payment Plan) Program in Reducing JKN Contribution Arrears at BPJS Health in Solok City. Qualitative research methods with a descriptive approach were used in this research which aims to describe phenomena that correspond to events in the field. The data collection techniques used in this research were interviews and documentation. The theory used in this research is the theory of Van Metter and Van Horn (1975), which includes policy size and objectives, resources, characteristics of implementing agents, attitudes/dispositions of implementers, inter-organizational communication and implementing activities, as well as the economic environment. , social, and political. The research results show that there are three forms of implementing the REHAB program, namely the REHAB Education Competition, outreach, and collaboration with the District Attorney's Office. However, in its implementation there are several problems such as the low interest of health facilities in participating in educational competitions, uneven outreach to the community due to limited infrastructure, and collaboration with the prosecutor's office which causes a negative impact on participants who are in arrears.